2011
DOI: 10.1177/1071181311551062
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Us Resilient to Interruptions? Understanding the Role of Individual Differences in Resumption

Abstract: Interruptions are an inescapable reality in our lives and they sometimes lead to unfortunate consequences. Most of the interruptions literature focuses on aspects of the interruption task that makes them more or less disruptive to performance. However, it is important to consider what might make a person resilient to the deleterious effects of interruptions. This research seeks to explore the individual performer and the specific cognitive aspects that might make someone better or worse at dealing with an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 13 publications
3
19
0
Order By: Relevance
“…Research indicates, for instance, that how closely an individual monitors and plans for interruptions, via executive control, mediates the relationship between multimedia interruptions and resultant stress (Tams et al, 2015), and that differences in working memory capacity (which is closely linked to executive functioning) is a predictor of the speed of task resumption following an interruption (Werner et al, 2011). …”
Section: Mobile Technology Use and Everyday Cognitive Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates, for instance, that how closely an individual monitors and plans for interruptions, via executive control, mediates the relationship between multimedia interruptions and resultant stress (Tams et al, 2015), and that differences in working memory capacity (which is closely linked to executive functioning) is a predictor of the speed of task resumption following an interruption (Werner et al, 2011). …”
Section: Mobile Technology Use and Everyday Cognitive Functioningmentioning
confidence: 99%
“…Interestingly, there is also some evidence suggesting that one’s susceptibility to cognitive disruption from mobile technology use, and the consequent impacts on academic success, might depend on the individual’s existing cognitive skill set; especially their ability to exert self-regulatory control over behavior. Research indicates, for instance, that how closely an individual monitors and plans for interruptions, via executive control, mediates the relationship between multimedia interruptions and resultant stress ( Tams et al, 2015 ), and that differences in working memory capacity (which is closely linked to executive functioning) is a predictor of the speed of task resumption following an interruption ( Werner et al, 2011 ).…”
Section: Mobile Technology Use and Everyday Cognitive Functioningmentioning
confidence: 99%
“…19 Some of this may depend on the a person's cognitive skill set, ability to exert self-regulatory control over behavior, interruptions and resultant stress and working memory capacity as a predictor of the speed of task resumption following an interruption. 68 Other things like diet, exercise, sleep and mood may also indirectly affect measurement of these issues.…”
Section: Other Cognitive Functionsmentioning
confidence: 99%
“…Cades et al (2011) reported similar findings showing that participants were significantly slower to resume a task when completing an N-back interruption task with a 1-back load compared to a shadowing interruption task (equivalent to 0-back). Additionally, individual working memory capacity has been shown to be reliably associated with interrupted task performance (Meys & Sanderson, 2013;Werner et al, 2011). These lines of evidence highlight working memory as an important cognitive component that can influence the resumption process following an interruption.…”
mentioning
confidence: 96%
“…We hypothesized that active stimulation of two target brain regions, the left and right DLPFC, would reduce resumption time in the interrupted task. There were three sources of evidence that provided the rationale for the choice of these sites: (a) the close link between working memory and DLPFC activation (D'Esposito et al, 1998;McCarthy et al, 1994), (b) the finding that tDCS applied over either the left or right DLPFC enhances working memory (Andrews et al, 2011;Berryhill & Jones, 2012;Ferrucci et al, 2008;Fregni et al, 2005;Javadi et al, 2012;Richmond et al, 2014), and (c) evidence pointing to close associations between working memory and interrupted task performance (Cades, 2007;Meys & Sanderson, 2013;Monk et al, 2008;Werner et al, 2011). In addition, in order to investigate the specificity of active stimulation with tDCS, we chose two control conditions: active stimulation of the left primary motor cortex, which enhances motor learning (Nitsche et al, 2003;Reis et al, 2009) but not working memory, and sham stimulation of the right DLPFC.…”
mentioning
confidence: 99%